Antigenic variation in African trypanosomes: the importance of chromosomal and nuclear context in VSG expression control. (10th October 2013) - Glover, Lucy; Hutchinson, Sebastian; Alsford, Sam; McCulloch, Richard; Field, Mark C.; Horn, David
Summary African trypanosomes are lethal human and animal parasites that use antigenic variation for evasion of host adaptive immunity. To facilitate antigenic variation, trypanosomes dedicate approximately one third of their nuclear genome, including many minichromosomes, and possibly all sub‐telomeres, to variant surface glycoprotein (VSG) genes and associated sequences. Antigenic variation requires transcription of a single VSG by RNA polymerase I (Pol‐I), with silencing of other VSGs, and periodic switching of the expressed gene, typically via DNA recombination with duplicative translocation of a new VSG to the active site. Thus, telomeric location, epigenetic controls and monoallelic transcription by Pol‐I at an extranucleolar site are prominent features of VSGs and their expression, with telomeres, chromatin structure and nuclear organization all making vitally important contributions to monoallelic VSG expression control and switching. We discuss VSG transcription, recombination and replication control within this chromosomal and sub‐nuclear context.